Chromosomal aberrations of cancer–testis antigens in myeloma patients. Issue 3 (13th May 2014) - Curioni‐Fontecedro, Alessandra; Martin, Vittoria; Vogetseder, Alexander; Knuth, Alexander; Moch, Holger; Soldini, Davide; Tinguely, Marianne
Abstract: Cancer–testis antigens (CTAgs) play a major role in the immune response against cancer, but their biological functions in germ and cancer cells is still unclear. MAGE‐C1 and MAGE‐C2 are two CTAgs located at the Xq27 region of chromosome X and frequently expressed in multiple myeloma. Chromosomal rearrangements often occur in myeloma. We therefore investigated whether numerical and structural chromosomal aberrations correlate with their protein expression in primary multiple myelomas. To this aim, we designed new fluorescence in situ hybridization probes specific for the MAGE region in the Xq27 region and evaluated simultaneously aberrations of the X chromosome centromere. The comparison of MAGE copy number and chromosome X status revealed that MAGE copy number changes occurred in 6/43 (14%) cases, independent of concomitant X chromosome alterations. These numerical aberrations are less frequent than the expression of MAGE‐C1 and MAGE‐C2 (63% and 27% of patients, respectively) and do not always correlate with MAGE‐C1 and MAGE‐C2 expressions, suggesting alternative regulatory mechanisms in the expression of these genes. Copyright © 2014 John Wiley & Sons, Ltd.